Geographic Information System Locating Hospitals and Police Stations Based on Android - Achmad Junafan (Journal of Intelligent Decision Support System (IDSS), 2021)
Currently technology is developing rapidly. By using a geographic information system and internet service media navigation system or GPS (Global Positioning System) found on the android smartphone platform, Google Maps and Google Services which are virtual map products, free and online. Where people can access maps anywhere and anytime when needed. However, the google map does not show the location of the police station and hospital as a whole, therefore it is necessary to develop a geographic information system (GIS) for the location of police stations and hospitals in the Sidoarjo Region. In this study, researchers created an Android-based automatic geographic information system for finding the location of hospitals and police stations.